READINESS FOR ARTIFICIAL INTELLIGENCE ADOPTION IN DIGITAL-BASED EDUCATIONAL INFORMATION SYSTEM MANAGEMENT: A CASE STUDY AT SMK NEGERI 1 TANJUNG - Farida Herawati; Ahmad Suriansyah; Aslamiah Aslamiah (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study analyzes the readiness for adopting Artificial Intelligence (AI) in educational information system management at SMK Negeri 1 Tanjung, Tabalong Regency, with a focus on digital promotion and new student enrollment. Employing a descriptive qualitative approach with an instrumental case study design, data were collected through in-depth interviews, observation, and documentation involving thirteen purposively selected informants, and analyzed using the Miles and Huberman interactive model. The findings indicate that the school is at the pre-adoption phase, characterized by platform-based digitalization but without substantive integration of algorithm-based AI systems. Three primary barriers were identified: low AI literacy among educational staff, fragmented information system data, and the absence of formal digital transformation policies. As the principal empirical and practical contribution, this study produces a contextual four-stage AI adoption roadmap tailored for vocational secondary schools, providing a realistic and evidence-based guide for progressing from pre-adoption to full AI-MIS integration.